“NUTRI EMO” game-based nutrition education: innovation of mother's knowledge improvement program to overcome children's nutrition problems in Buleleng, Bali - Kuswandari, Luh Shanti; Andani, Dian Puteri (BKM Public Health and Community Medicine, 2021)
Objective: Mother’s lack of nutrition knowledge is one of the risk factors that cause child malnutrition in Bali. Existing nutrition education program is not sufficient due to a lack of awareness, and the attendance only becomes a formality without understanding information and the desire to apply. This program innovation aims to improve mothers' understanding of the materials delivered, and it is expected that mothers can apply them into daily life. Content: Nutrition education programs have been conducted. Nevertheless, it needs innovations in order to run more effectively. Game-based nutrition education is one of the innovations to make the delivery of education more engaging. "Nutri Emo" is one of the game innovations that combines game methods and demonstrations to increase the interest and attention of mothers in Buleleng Regency to be active and participative when receiving the materials delivered. Each point earned from the game will be replaced by a beam. The beams are arranged and illustrated as child growth. It aims to show the mother that if she nourished the child well, the growth of the child will also be good. At the end of the program, we play the game "Ibu Pintar" to evaluate the mother's understanding of education. This program potentially increases the mother's understanding of the material presented and motivated her to make changes. Meanwhile, attractive program is also needs support from the community leader to be succed. Involving the head of the village's wife is the best option, as they are one of the figure close to the mothers in the village. Advocacy to the Village Head's Wife has great potential for the sustainability of the program. The village head's wife's support for this activity can increase community participation in this education program.